Limited arbitrage in mergers and acquisitions - Baker, Malcolm; Savaşoglu, Serkan (Journal of Financial Economics, 2002)
A diversified portfolio of risk arbitrage positions produces an abnormal return of 0.6–0.9% per month over the period from 1981 to 1996. We trace these profits to practical limits on risk arbitrage. In our model of risk arbitrage, arbitrageurs’ risk-bearing capacity is constrained by deal completion risk and the size of the position they hold. Consistent with this model, we document that the returns to risk arbitrage increase in an ex ante measure of completion risk and target size. We also examine the influence of the general supply of arbitrage capital, measured by the total equity holdings of arbitrageurs, on arbitrage profits.